Constructing S-scheme g-C3N4/ZnIn2S4 heterojunctions via synergistic morphological and interfacial engineering for bifunctional H2 evolution and pollutant degradation - Xiaodong Li; Min Chao; Yunhang Wang; Yanzhuang Duan; Chunjia Luo; Xi Chen; Luke Yan (Journal of Environmental Chemical Engineering, 2026)

Eucalypt Leaf Litter and a Drying-Rewetting Cycle Shape Wetland Soil-Water Nutrient Dynamics: A Laboratory Microcosm Study - Rui Yan; Luke Mosley; Petra Marschner (Wetlands, 2026)
This study used laboratory column microcosms with River Murray (Australia) wetland soils and water to examine how drying-rewetting (DRW) and river red gum ( Eucalyptus camaldulensis ) litter inputs interactively affect nitrogen (N), phosphorus (P), and carbon dynamics across soil, pore water, and overlying water. We quantified N and P species and dissolved organic carbon (DOC) under two water regimes (constant submergence versus DRW) with and without litter addition to resolve cross-compartment responses at the aquatic-terrestrial interface. DRW enhanced net inorganic-N mobilization, resulting in pronounced post-rewetting pulses in pore-water and overlying-water N (especially NH 4 + ) compared to constant submergence, with concentrations gradually converging during prolonged inundation. Conversely, total P and inorganic P (P i ) were higher under constant submergence, consistent with sustained reducing conditions promoting P release in solution. Although litter inputs did not substantially alter total nutrient levels in overlying water, they shifted pore-water chemistry by increasing the proportion of inorganic P and strongly elevating DOC. Following rewetting, DOC increased sharply in litter-amended treatments, ~ 2.9-fold in overlying water and ~ 16.8-fold in pore water, compared with no-litter treatments. Litter addition also reduced nitrate availability in soil and pore water during resubmergence, consistent with stronger microbial N retention and/or NO 3 − consumption under rapidly re-established reducing microsites after rewetting. Overall, DRW and litter inputs interact to amplify short-lived C and N pulses while modifying P speciation, with implications for predicting nutrient availability and water-quality risk in wetlands experiencing increasingly variable hydrological regimes.

Protein/polysaccharide composite nanocoating based on amyloid-like aggregation for fresh-cut fruits preservation - Guichen Liu; Rong Liu; Chengyu Fu; Xiang Hu; Ke Li; Luke Yan; Peng Yang; Jian Zhao (Chemical Engineering Journal, 2025)

One-step recovery of precious metal ions from oil/water emulsions by multifunctional CNTs-PAH/MXene membrane for further recycling utilization - Xiaohan Niu; Mengting Li; Chunjia Luo; Min Chao; Xushuai Chen; Luke Yan (Journal of Environmental Chemical Engineering, 2025)

Inorganic-rich solid electrolyte interphase and oriented (002) crystal plane extension for reversible zinc metal anode - Biyao Du; Jingzhu Chen; Yang Xu; Zhuoran Lv; Peng Ying; Wujie Dong; Luke Yan; Hui Bi; Fuqiang Huang (Chemical Engineering Journal, 2025)

Salt-resistant MXene-charge gradient hydrogel evaporator with boosted water transport for efficient photothermal desalination - Xushuai Chen; Panpan Zhang; Xi Chen; Chunjia Luo; Min Chao; Luke Yan (Desalination, 2024)

Superhydrophobic sand evaporator with core-shell structure for long-term salt-resistant solar desalination - Qingyang Xue; Peng Xiao; Jincui Gu; Wenqin Wang; Luke Yan; Tao Chen (Water Research, 2024)

Thickness-variation-insensitive near-infrared quantum dot LEDs - Wan-Shan Shen; Yang Liu; Luke Grater; So Min Park; Haoyue Wan; Yan-Jun Yu; Jia-Lin Pan; Fan-Cheng Kong; Qi-Sheng Tian; Dong-Ying Zhou; Zeke Liu; Wanli Ma; et al. (Science Bulletin, 2023)

Euplectella aspergillum inspired PPAN@g-C3N4 fibrous membrane with abundant micro/nano pores for high-throughput wastewater purification - Peng Chai; Chunjia Luo; Jincui Gu; Fan Yu; Min Chao; Xi Chen; Luke Yan (Journal of Environmental Chemical Engineering, 2023)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Characterization of a large sex determination region in Salix purpurea L. (Salicaceae) - Ran Zhou; David Macaya-Sanz; Eli Rodgers-Melnick; Craig H. Carlson; Fred E. Gouker; Luke M. Evans; Jeremy Schmutz; Jerry W. Jenkins; Juying Yan; Gerald A. Tuskan; Lawrence B. Smart; Stephen P. DiFazio (Molecular Genetics and Genomics, 2018)